واقع ممارسة العلاقات العامة في الإدارة المحلية دراسة ميدانية بمصالح ولاية سوق أهراس - كبير لطيفة (My University, 2019)
Abstract: Local administration does not fully comprehend the function of public relations, which hinders local administrative work and its effectiveness. There is also a lack of local administration’s commitment to gaining the confidence of the local public and external stakeholders. This is due to the many problems that are intertwined, such as bureaucracy in management and informing local public opinion, and the lack of responsibility for destroying the desired image among the local public and external stakeholders, in addition to the rest of the communication problems that are intertwined with it, whether inside or outside the unit. Finally, we hope that this study will be an additional building block for scientific research in the field of public relations. We also hope that this study has been able to provide an accurate and objective picture of the reality of public relations in the local administration. Sahel, Souk Ahras Province. We hope that it will arouse the interest of officials in the local administration in the field of public relations in the local administration and its significant role in achieving stability and success. -------------------------- ملخص: لا تُدرك الإدارة المحلية وظيفة العلاقات العامة بشكل كامل، مما يُعيق عملها وفعاليتها. كما يُلاحظ ضعف التزامها بكسب ثقة الجمهور المحلي والجهات الخارجية المعنية. ويعود ذلك إلى العديد من المشاكل المتشابكة، كالبيروقراطية في الإدارة وإعلام الرأي العام المحلي، وغياب المسؤولية عن تشويه الصورة المرجوة لدى الجمهور المحلي والجهات الخارجية المعنية، بالإضافة إلى باقي مشاكل الاتصال المتشابكة معها، سواءً داخل الوحدة أو خارجها. وأخيرًا، نأمل أن تُشكل هذه الدراسة لبنة إضافية للبحث العلمي في مجال العلاقات العامة، وأن تكون قد استطاعت تقديم صورة دقيقة وموضوعية عن واقع العلاقات العامة في الإدارة المحلية. الساحل، ولاية سوق أهراس. ونأمل أن تُثير اهتمام المسؤولين في الإدارة المحلية بمجال العلاقات العامة في الإدارة المحلية ودوره الهام في تحقيق الاستقرار والنجاح.
Keywords: العلاقات العامة، الإدارة المحلية